Populism: perspectives from legal philosophy - Kirste, Stephan; Paulo, Norbert (Archiv für Rechts- und Sozialphilosophie, 2021)
Intro -- Content -- Introduction (STEPHAN KIRSTE / NORBERT PAULO) -- Part I: Foundations -- The Two Faces of Populism. How the Populist Performance Challenges Liberal Democracy (BART VAN KLINK) -- The Populist Reversal of Constitutionalism. From the Dialectical Unity of Democracy and the Rule of Law to the Negative Dialectic of Populist's Anti-Institutionalism (STEPHAN KIRSTE) -- Böckenförde's Ethos of Legality. On the Foundations of Constitutional Democracy and the Populist Challenge to It (OLIVER W. LEMBCKE) -- What Gustav Radbruch Teaches Us about (Authoritarian) Populism. Lies by Officials should not be Referred to as Populism because they are a Genuine Threat to the Democratic Legal Culture. (LANDO KIRCHMAIR) -- Part II: Populism and the Political -- The Shortcomings of Left Populism (KATARZYNA ELIASZ) -- Populism as Anti-Pluralism (JUDITH ZINSMAIER) -- The Populist Call for the Reanimation of a Silenced and Rigidified Democracy (GREGOR BERGER) -- The Challenge of Migration. Is Liberalism the Problem? (KARSTEN SCHUBERT) -- Part III: Case Studies: Populism in Italy and Brazil -- The Italian Five Star Movement and the Techno-populist Dystopia. Direct Democracy and the End of Politics (LUCIA CORSO / LETTERIA G. FASSARI) -- Democracy Without People. The new right-wing populism in Brazil and the paradox of democracy (JULIANA NEUENSCHWANDER / MARCUS GIRALDES) -- Populism, Democracy and the Rule of Law in Today's Brazil (MARCOS AUGUSTO MALISKA) -- Part IV: Epistemic Issues -- Populism, Democracy and Epistemic Injustices (GOTTFRIED SCHWEIGER) -- Authoritarian Populism and Epistemic Injustice in the Context of the Vulnerable Legal Subject (GÜLRIZ UYGUR) -- Populism, Political Fallibility, and the Pandemic (ADRIANO MANNINO) -- Expecting Voters to be Informed and Rational (NORBERT PAULO) -- Populism and Political Theology: Two Accounts (AHMAD BOSTANI).